The Influence of Motivation, Capability, and Knowledge Management on Productivity: A Systematic Literature Review: Pengaruh Motivasi, Kapabilitas, dan Manajemen Pengetahuan terhadap Produktivitas : Tinjauan Literatur Sistematis - Pepen S. Almas; Hapzi Ali (OGZ Research & Publishing, 2026)
Abstract: Productivity is one of the most important indicators determining organizational success in achieving goals and maintaining competitiveness. Previous studies have demonstrated that motivation, capability, and knowledge management contribute significantly to productivity improvement; however, the findings remain scattered across different contexts and research approaches. Objective: This study aims to analyze and synthesize previous research findings regarding the influence of motivation, capability, and knowledge management on productivity through a Systematic Literature Review (SLR) approach. Methodology: The study followed the PRISMA 2020 guideline, comprising identification, screening, eligibility, and inclusion stages to select relevant academic articles from various scholarly databases. The reviewed articles were published between 2015 and 2025 and met the established inclusion criteria. Data were analyzed using narrative synthesis and thematic analysis to identify patterns of relationships among variables. Research Results: The findings indicate that motivation positively influences productivity by enhancing employee engagement, commitment, and work enthusiasm. Capability contributes to productivity through the development of competencies, skills, and adaptability. Furthermore, knowledge management improves productivity through effective processes of knowledge creation, storage, sharing, and application within organizations. The study concludes that motivation, capability, and knowledge management are critical factors that positively affect productivity and can serve as a theoretical foundation for developing hypotheses in future empirical research.